Analisis Manajemen Modal Kerja Dan Inovasi Pada Produk Terhadap Laba Usaha Guna Mengembangkan Umkm Ikan Asin Hj.Faridah Di Desa Klampis Timur - Wardiah, Malahatul; Dwi Purnomo, Arie Setyo (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aims to analyze working capital management, new innovations in products on operating profit to develop salted fish SMEs in East Klampis village. Working capital, namely current assets in a business, product innovation, new ideas to get maximum profits. The research method used is qualitative with a qualitative descriptive approach. The data used in this study were obtained by conducting interviews, observation and documentation directly with salted fish business owners, salted fish business workers (employees), and salted fish buyers. The results of this study indicate that working capital management and new product innovations can generate maximum profits. The results are more precise and more profitable when carrying out product innovation by getting a profit of 42% compared to before carrying out product innovation, only getting a profit of 28% and 33%.